Hubungan Antara Penerapan Aturan Pola Makan MPASI Dengan Status Gizi Anak Usia di Bawah Dua Tahun di Kelurahan Jagir Surabaya - Audia Putri, Fany; Garianto, Efyluk; Purwatiningrum, Prijanti Eka; Sudiarta, Ketut Edy (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Introduction: The WHO recommends implementing feeding rules early in life to prevent child malnutrition. Providing good complementary foods requires attention to timeliness, adequate nutrition, safety and responsive delivery. Objective: This study aims to determine the relationship between the application of complementary feeding guidelines and the nutritional status of children under 2 years of age in Kelurahan Jagir Surabaya. Methods: An observational-analytic, cross-sectional study was conducted in 15 Integrated Health Service Post. 91 Mothers and children aged 6-24 months were selected using a purposive sampling method. The research instrument used anthropometric measurement data and questionnaires. This study analyzed the data using Spearman's rho correlation test (p < 0.05). Results: Spearman's rho analysis showed a relationship between the application of complementary feeding rules and the nutritional status indices BB/U and BB/PB (p < 0,001). However, there was no relationship between the application of complementary feeding rules and the nutritional status of the TB/U index (p = 0.307). The application of complementary feeding rules is associated with weight-for-age and weight-for-height status, but not with height-for-age, which reflects chronic malnutrition. Conclusion: These findings emphasize that the application of Basic Feeding Rules contributes to better weight gain in infants and young children, reinforcing the importance of pediatricians and health workers in complementary feeding education and counselling as a promotive and preventive measure in pediatrics. Thus, education and guidance for parents and health workers to improve complementary feeding practices are paramount to support improvements in children's nutritional status.